2005
DOI: 10.1111/j.1365-3148.2005.00577.x
|View full text |Cite
|
Sign up to set email alerts
|

Pseudocontamination of blood components with Burkholderia cepacia during quality controls

Abstract: We report on a pseudooutbreak of Burkholderia cepacia because of the use of a contaminated disinfectant during quality controls in a university blood bank. No septic reactions associated with transfusions had been reported in patients over the last 6 months. Analysis of the individual quality control procedures showed that a disinfectant based on a quaternary ammonium compound (QAC) had been used in order to disinfect the rubber stopper of the blood culture bottle. B. cepacia was found in a sample taken from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Delladet was effective against all bacterial isolates on stainless steel and epoxy surfaces, but it was not effective against A. lwoffii, B. cepacia and E. coli on ceramic. That was in parallel with Ebner et al (2005) who reported that B. cepacia was isolated as a contaminant from quaternary ammonium-based disinfectant. Although it disrupts cell membrane and leads to cell lysis and bacterial death (Jennings et al 2015), for the presence of B. cepacia in the water system, using delladet as disinfection is not the most suitable solution.…”
Section: Discussionsupporting
confidence: 73%
“…Delladet was effective against all bacterial isolates on stainless steel and epoxy surfaces, but it was not effective against A. lwoffii, B. cepacia and E. coli on ceramic. That was in parallel with Ebner et al (2005) who reported that B. cepacia was isolated as a contaminant from quaternary ammonium-based disinfectant. Although it disrupts cell membrane and leads to cell lysis and bacterial death (Jennings et al 2015), for the presence of B. cepacia in the water system, using delladet as disinfection is not the most suitable solution.…”
Section: Discussionsupporting
confidence: 73%
“…The bactericidal action of the quaternary ammonium compounds has been attributed to the inactivation of energy-producing enzymes, denaturation of essential cell proteins, and disruption of the cell membrane. A pseudo-outbreak of B. cepacia bacteremia was traced to the use of a contaminated quaternary ammonium compound to disinfect the rubber stoppers of blood culture bottles (21).…”
Section: Disinfectantsmentioning
confidence: 99%
“…Exposure of pathogens to low and ineffective concentrations may also occur by failing to remove organic material (including biofilms), adsorption of QAC to the wipe material, or application of products at a suboptimal pH [ 29 , 69 , 117 , 142 ]. QAC-based disinfectants should not be used to wipe the tops of blood culture bottles prior to injecting blood into culture bottles [ 105 ]. Because multiple outbreaks related to contaminated BAC-based antiseptics have occurred, the Centers for Disease Control and Prevention Guideline for Disinfection and Sterilization in Healthcare no longer lists QAC-based antiseptics as one of the recommended uses of QACs in healthcare settings [ 34 ].…”
Section: Discussionmentioning
confidence: 99%